PERFORATED PEPTIC ULCER: DIAGNOSTIC STRATEGIES - Gomes, Bruno da Silva; de Macedo, Ryan Rafael Barros; Vieira, Carolina Sena; Oliveira, Juliana Cristina Santana Lima Queiroz; Baltazar Júnior, Orlando; de Azevedo, Gabriel Felicio; Louzada, Rafael Cardoso; Bolzan, Amanda Camilla Schmidt; Costa, Fernando Gomes; dos Santos, José Ricardo; Silva, Vitor de Castro; Zancan, Luiza Favaro; et al. (Seven Editora, 2026)
Perforated peptic ulcer (PPU) represents a surgical emergency associated with high morbidity and mortality, whose evolution is directly related to the speed of diagnosis and adequate prognostic stratification. Although the incidence of peptic ulcer disease has decreased, perforation remains a relevant complication, especially in elderly patients, users of non-steroidal anti-inflammatory drugs, and those with Helicobacter pylori infection. The diagnosis of PPU is based on the correlation between clinical findings, laboratory tests, and imaging methods. Computed tomography is considered the gold standard, allowing diagnostic confirmation, identification of the perforation site, and assessment of the extent of peritonitis. Laboratory tests, including complete blood count, C-reactive protein, serum lactate, and renal function assessment, play a complementary role in identifying the systemic inflammatory response and stratifying severity. The use of prognostic scores, such as Boey, ASA, and Mannheim Peritonitis Index, contributes to the prediction of outcomes and to guiding surgical management. Thus, the present study aims to review contemporary diagnostic strategies for perforated peptic ulcer, highlighting the importance of early recognition and systematic evaluation in reducing complications and mortality associated with the disease.DOI: https://doi.org/10.56238/sevened2026.002-009